HbA1C AS AN INDEX OF GLYCEMIC STATUS IN OBESE TYPE 2 DIABETICS - S, Shabana; K, Ramya; T.V.D, Sasisekhar; Kumar A, Santosh (International Journal of Clinical and Biomedical Research, 2017)
Introduction: Type 2 diabetes has become a worldwide issue with the dramatic increase in incidence and prevalence over the past two decades. As the epidemiological burden of diabetes increases, the economic burden on individuals and nation is expected to rise. Obesity being one of the major risk factor for development of T2DM and its complication, glycemic control is crucial for management of diabetes. HbA1c is an index of long term glycemic status of diabetic subjects and has become the gold standard test around the world for initiation of treatment in diabetics. Aims: The aim of this study was to determine the association of obesity with T2DM and to correlate dysglycemia with obesity. Material and Methods: A total of 100 type 2 diabetics were enrolled for the study. The subjects were categorized based on the revised consensus guidelines for India for generalized obesity and abdominal obesity. Results: The results of the study showed that gender wise there was no significant difference of the various clinical and biochemical characteristics except for the duration of diabetes. Subjects of this study were mostly overweight and obese having abdominal obesity. A significant correlation was seen between the glycemic and metabolic status of the diabetic study population. Conclusion: Overall an increasing trend of dysglycemia in diabetic subjects with normal BMI, overweight to obese was observed. The prevalence of both central and peripheral obesity was increased in the diabetic subjects. KEY WORDS: HbA1c; Obesity; Type 2 diabetes mellitus.